1973
DOI: 10.1111/j.1476-5381.1973.tb08190.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic control of tendon jerk reflexes in man

Abstract: Summary Tendon jerk responses and H reflexes were recorded from conscious human volunteers before and after intravenous injection of methylamphetamine, thymoxamine and propranolol, and during intravenous infusion of noradrenaline. Methylamphetamine produced a significant increase in the amplitude of the tendon jerk, whereas noradrenaline had no effect in doses which caused a greater pressor response than methylamphetamine. Thymoxamine produced a dose‐related reduction in the tendon jerk. Propranolol had no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
(16 reference statements)
2
15
1
Order By: Relevance
“…Comparison with previously published results (Phillips et al, 1973) suggests that thymoxamine was more potent than chlorpromazine in depressing the triceps surae jerk, and three times as potent as indoramin. Isolated tissue experiments have shown consistently that thymoxamine is a weaker ax-adrenoceptor blocker than chlorpromazine or indoramin (Birmingham & Szolcsanyi, 1965;Collis & Alps, 1973;Gorlitz & Frey, 1973;Variava & Turner, 1973;Sugden, 1974).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Comparison with previously published results (Phillips et al, 1973) suggests that thymoxamine was more potent than chlorpromazine in depressing the triceps surae jerk, and three times as potent as indoramin. Isolated tissue experiments have shown consistently that thymoxamine is a weaker ax-adrenoceptor blocker than chlorpromazine or indoramin (Birmingham & Szolcsanyi, 1965;Collis & Alps, 1973;Gorlitz & Frey, 1973;Variava & Turner, 1973;Sugden, 1974).…”
Section: Discussionmentioning
confidence: 72%
“…The amplitude of the triceps surae jerk was measured isometrically using the method previously described by Phillips et al (1973), modified to the extent that the subjects were lying instead of sitting. A standard tap was delivered to the Achilles tendon by a hammer dropped from a fixed height.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since blockade of peripheral a-adrenoceptors would account for the reduced hypertensive response but not the reduced bradycardia (which was mediated by increased cardiac vagal tone) it is possible that thymoxamine antagonized a-adrenoceptors in the anterior hypothalamus. Since thymoxamine readily penetrates the CNS (Pruvot, Agneray & Hdquet, 1969;Phillips, Richens & Shand, 1973), it was not possible to determine the contribution made by increased sympathetic drive to noradrenaline-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Descending adrenergic pathways have been described (Dahlstrbm & Fuxe, 1965;Fuxe, H6kfelt & Ungerstedt, 1969), and Ellaway & Pascoe (1968) have suggested that noradrenaline may be an excitatory transmitter involved in the control of fusimotor activity. An adrenergic control of tendon jerk reflexes in man has also been suggested (Phillips, Richens & Shand, 1973).…”
Section: Experiments In the Dogmentioning
confidence: 99%